2016
DOI: 10.1111/2041-210x.12542
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in biological monitoring: a framework for data collection and analysis to account for multiple sources of sampling bias

Abstract: Summary Biological monitoring programmes are increasingly relying upon large volumes of citizen‐science data to improve the scope and spatial coverage of information, challenging the scientific community to develop design and model‐based approaches to improve inference. Recent statistical models in ecology have been developed to accommodate false‐negative errors, although current work points to false‐positive errors as equally important sources of bias. This is of particular concern for the success of any mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 54 publications
0
81
0
Order By: Relevance
“…While the ideal way to measure the value of a habitat would be to estimate survival and reproduction parameters based on long‐term demographic and/or movement studies of species showing a representative range of ecological and behavioural traits (Milder et al, ; Sekercioglu, Loarie, Brenes, Ehrlich, & Daily, ), these are rarely feasible in tropical ecosystems. Our results show that occupancy and abundance models generated from the wide‐scale application of simple sampling methodologies (Irizarry et al, ; Ruiz‐Gutiérrez, Hooten, & Campbell Grant, ) may neglect important differences in habitat preference and performance. Capture data allow for the exploration of habitat–species relationships at a resolution intermediate between these two extremes (Ruiz‐Gutiérrez et al, ; Sekercioglu, ), but to increase the reliability of our inference, we need further research into the relationships between individual‐level data and consequences at the population level.…”
Section: Discussionmentioning
confidence: 79%
“…While the ideal way to measure the value of a habitat would be to estimate survival and reproduction parameters based on long‐term demographic and/or movement studies of species showing a representative range of ecological and behavioural traits (Milder et al, ; Sekercioglu, Loarie, Brenes, Ehrlich, & Daily, ), these are rarely feasible in tropical ecosystems. Our results show that occupancy and abundance models generated from the wide‐scale application of simple sampling methodologies (Irizarry et al, ; Ruiz‐Gutiérrez, Hooten, & Campbell Grant, ) may neglect important differences in habitat preference and performance. Capture data allow for the exploration of habitat–species relationships at a resolution intermediate between these two extremes (Ruiz‐Gutiérrez et al, ; Sekercioglu, ), but to increase the reliability of our inference, we need further research into the relationships between individual‐level data and consequences at the population level.…”
Section: Discussionmentioning
confidence: 79%
“…Environment–ecology relationships in this study showed substantial differences between years (drought versus flood) and across taxonomic groups. Using biological data to inform policies and models can improve the likelihood of achieving desired results (King et al., ; Poff et al., ), yet there is a great deal of variation inherent in the collection of such data (Hurlbert, ; Ruiz‐Gutierrez, Hooten, & Grant, ). While long‐term monitoring studies designed to assess year‐to‐year temporal variation at the same site would be the ideal way to better understand environmental flow relationships (MacDonald & Cote, ), limitations of time and funding make this an impractical option.…”
Section: Resultsmentioning
confidence: 99%
“…They found that simultaneously estimating both false-negative and false-positive error rates is computationally challenging, as any set of detection histories can be equally well explained by multiple sets of parameter values (Guillera-Arroita, Lahoz-Monfort, van Rooyen, Weeks, & Tingley, 2017). Other approaches have made use of calibration experiments to experimentally infer false-positive error rates under controlled conditions and use these to inform analysis of survey data (Chambert et al, 2015;Guillera-Arroita et al, 2017;Lahoz-Monfort, Guillera-Arroita, & Tingley, 2016;Ruiz-Gutierrez, Hooten, & Grant, 2016). Subsequent developments have developed alternative solutions to this identifiability issue by utilizing extra information to inform the detection parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Royle and Link (2006) addressed this issue by forcing a constraint upon the model that the false-positive error rate must be lower than the true detection rate. These approaches have been successfully applied, however performing calibration experiments to inform false-positive error rates in survey data is often impractical (though see McClintock, Bailey, Pollock, and Semons (2010) and Ruiz-Gutierrez et al (2016) for a successful application), and there may be situations where secondary datasets are not available. Typically this involves jointly analyzing the dataset of interest alongside a second, independent dataset at which a subset of sites are monitored using secondary detection methods in which the probability of false-positive observations is considered impossible (Chambert, Miller, & Nichols, 2015;Miller et al, 2011Miller et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%